Interplay of upper respiratory tract microbiota, ımmune response, and molecular dynamics in SARS-CoV-2 infection: Microbiota and Immunity in SARS-COV-2 - Sahar Abdul Wahhab Alsamarai; Waqas Saadi Mahmood; Ammar mohmed alwan; Melda Dölarslan (Cellular and Molecular Biology, 2025)
Understanding the interplay between upper respiratory tract microbiota, immune responses, and molecular changes is critical for improving the diagnosis and management of SARS-CoV-2 infections. In this study, we investigated the association between respiratory tract microbiota composition, immune markers, and molecular diagnostic parameters in 123 RT-PCR-confirmed COVID-19 patients. Co-infection rates with Gram-positive and Gram-negative bacteria were high, particularly in the nasopharynx (35.4% and 64.4%, respectively), highlighting the risk of secondary bacterial infections. Diagnostic evaluation showed that RT-PCR cycle threshold (Ct) values and serological markers (IgG, IgM) had high sensitivity and specificity for distinguishing infection status. Lower Ct values correlated with higher viral loads and acute infection, while antibody levels reflected immune response dynamics. Significant correlations were observed between bacterial presence and immune parameters such as ACE-2, FASL, and RBD. These findings underscore the importance of integrated diagnostic approaches that consider microbiota, molecular, and immunological markers for effective management of COVID-19 and its complications.